Distributed Temperature Sensing System Based on Brillouin Scattering Effect Using a Single-Photon Detector - Sheng, Liwen; Yan, Jisong; Li, Ligong; Yuan, Ming; Zhou, Shuai; Xu, Rui; Liu, Jiaqing; Nian, Fushun; Li, Long; Liu, Zhiming (International Journal of Optics, 2021)
Utilizing a single-photon detector, a novel direct-detection optical-fiber sensor for distributed measurement of temperature based on spontaneous Brillouin scattering is proposed and demonstrated experimentally. In our scheme, the ratio of the backscattered Rayleigh signal and the backscattered Brillouin anti-Stokes is adopted to retrieve the monitored temperature information along the optical fiber. Taking advantage of the high sensitivity of the single-photon detector, our proposed system achieves a dynamic range of 20 dB without any optical amplification. The obtainable dynamic range corresponds to a sensing distance of 120 km with a measured temperature error of 0.96°C. Furthermore, the proof-of-concept experiment demonstrates 1.2 m spatial resolution over 4.2 km sensing link with 1.24°C temperature error. Considering the performance we achieved now, and the increasing improvement of the fabrication technology of sing-photon detector, the photon-counting distributed Brillouin sensor is opening a door in the field of optical-fiber sensors.